Experimental evaluation of prophylactic and curative effect of a herbal drug Hemidesmus indicus R.Br. in drug induced ulcers in wistar albino rats - Bharadwaj, Shishira; Nayak, Shraddha (International Journal of Research in Medical Sciences, 2017)
Peptic Ulcers are the most common condition experienced by most of the people due to urbanized lifestyle. Hemidesmus indicus R.Br. is a herbal drug mentioned for its treatment in the ancient Indian traditional medicine. To compare the Prophylactic and Curative effects of aqueous and Alcoholic extracts of Hemidesmus indicus in Drug induced ulcers. Aqueous and Alcoholic extracts of the drug were studied for their ulcer healing activity in Wistar Albino rats. Ninety Wistar albino rats were divided into nine groups with one control, four prophylactic and four curative groups. Ulcers were induced with Indomethacin in a dose of 20 mg/kg body weight twice in a gap of 15 hours. Aqueous extract was given in a dose of 500 mg/kg body weight and alcohol in a dose of 100 mg/kg body weight. It was found that both have potential ulcer healing activity with alcoholic extract marginally better than aqueous extract. It can thus be concluded that Hemidesmus indicus R. Br is a effective drug in peptic ulcers.